IMPLEMENTASI PENCEGAHAN ‎PORNOGRAFI DALAM AL-QUR’AN (STUDI ‎PENAFSIRAN TERHADAP Q.S AN-NUR AYAT ‎‎30-31 MENURUT PROF. DR. HAMKA DALAM ‎TAFSIR AL AZHAR)‎ - Hidayatullah, Muhammad Hafiz (UIN Sumatera Utara Medan, 2024)
The development of technology and information has raised new issues for society. Among the problems that often occur and are difficult to prevent is pornography. Pornography does not recognize age limits; everyone can access it freely. The main factor that makes pornography difficult to prevent is the advancement of technology, which facilitates the dissemination of pornographic websites on social media. To address this issue, self-awareness is needed to prevent pornography, such as engaging in beneficial activities, avoiding spending time alone where others cannot see, and getting closer to Allah SWT by performing prayers, fasting, and reading the Qur'an. This study, titled